Policy Analysis of Inclusive-Based Education: Case Study of UIN Sunan Kalijaga - Luthfi Nurul Huda, Luthfi; Linda; Muhammad Syihabuddin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
As we know, education is an essential thing for every nation, one of which is the Indonesian state, because education is an important factor in the progress or retreat of a nation. The more optimal and integrated the education system, the more advanced the nation. According to Sutrisno, in a lecture on the subject of Islamic Education Policy and Leadership in Indonesia,